UNIX system V/386, release 3.2 : user's guide. (New Jersey : Prentice-Hall, 1989)
The material in this guide is organized into two major parts : an overview of the UNIX operating system and a set of tutorials on the main tools available on the UNIX system.
Part 1. UNIX system overview -- Part 2. UNIX system tutorials.
Includes bibliographical references and index.
Keywords: UNIX (COMPUTER PROGRAM LANGUAGE)